1994
DOI: 10.1116/1.587100
|View full text |Cite
|
Sign up to set email alerts
|

Gate oxide damage in a high density inductively coupled plasma

Abstract: A high density inductively coupled plasma (ICP) polycide etcher was studied by incorporating it into a 0.5 μm complementary metal–oxide–semiconductor process flow having a nominal 10 nm gate oxide. Polysilicon: oxide etch selectivity, sidewall profile, and critical dimension control were found to be good. Gate oxide damage was studied in detail using both antenna and large capacitor test structures in area- and edge-intensive configurations. No charge buildup was detected using the antenna structures, and dama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…-There has been a tremendous growth in knowledge in low temperature plasma materials processing/plasma etch science and technology since the first ALE studies. Examples are a) control of ionization, dissociation and uniformity across wafer, 1,3,107,108 b) ion energy control, 109 including using shaped waveforms, 96 c) pulsed plasma science and technology, 5 d) control of wafer charging and damage effects, [110][111][112] e) plasma characterization and metrology, 113,114 f) understanding of the control of plasma-polymer interactions, Line Edge Roughness, Line Width Roughness, CD and CD variation, 115 advanced modeling and simulations of all of the above, 116 and tremendous growth in advanced hardware engineering and capabilities.…”
Section: Scientific and Technological Basis Of Alementioning
confidence: 99%
“…-There has been a tremendous growth in knowledge in low temperature plasma materials processing/plasma etch science and technology since the first ALE studies. Examples are a) control of ionization, dissociation and uniformity across wafer, 1,3,107,108 b) ion energy control, 109 including using shaped waveforms, 96 c) pulsed plasma science and technology, 5 d) control of wafer charging and damage effects, [110][111][112] e) plasma characterization and metrology, 113,114 f) understanding of the control of plasma-polymer interactions, Line Edge Roughness, Line Width Roughness, CD and CD variation, 115 advanced modeling and simulations of all of the above, 116 and tremendous growth in advanced hardware engineering and capabilities.…”
Section: Scientific and Technological Basis Of Alementioning
confidence: 99%
“…[1][2][3][4] ''Ion and electron currents do not have to balance locally through the rf cycle, although there must be a net balance over the electrode as a whole.'' [1][2][3][4] ''Ion and electron currents do not have to balance locally through the rf cycle, although there must be a net balance over the electrode as a whole.''…”
Section: Understanding the Problemmentioning
confidence: 99%
“…It is well known that the accumulation of electrons on the SiO 2 layer causes charging damage to the gate SiO 2 layer. [17][18][19][20][21][22] It has been reported that SiO 2 damage during SiO 2 deposition and etching with a plasma process is caused by the accumulated electrical charges passing through the SiO 2 layer, where the charges are supplied to the gate electrodes of the antenna metal oxide semiconductor (MOS) capacitor from the plasma during the plasma process. [23][24][25] When the metal layer is deposited, it forms islands on the SiO 2 layer upon magnetron sputtering, and electrical charges accumulate on the SiO 2 layer.…”
Section: Introductionmentioning
confidence: 99%